2016
DOI: 10.1080/19491034.2016.1162933
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding nuclear size and shape

Abstract: Size and shape are important aspects of nuclear structure. While normal cells maintain nuclear size within a defined range, altered nuclear size and shape are associated with a variety of diseases. It is unknown if altered nuclear morphology contributes to pathology, and answering this question requires a better understanding of the mechanisms that control nuclear size and shape. In this review, we discuss recent advances in our understanding of the mechanisms that regulate nuclear morphology, focusing on nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
58
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 206 publications
4
58
0
3
Order By: Relevance
“…6B). Previous studies have shown that nuclear shape and size can influence gene transcription and access of transcriptional machinery to DNA (76)(77)(78). Surprisingly, gene families associated with the transcriptional activity are suppressed, and we do not observe dynamic changes concordant with changes in nucleus shape and size observed between cells on the different fiber networks.…”
Section: Gene-expression Analysissupporting
confidence: 46%
See 1 more Smart Citation
“…6B). Previous studies have shown that nuclear shape and size can influence gene transcription and access of transcriptional machinery to DNA (76)(77)(78). Surprisingly, gene families associated with the transcriptional activity are suppressed, and we do not observe dynamic changes concordant with changes in nucleus shape and size observed between cells on the different fiber networks.…”
Section: Gene-expression Analysissupporting
confidence: 46%
“…Our current and future studies are aimed at discerning the mechanisms of drug resistance in our in vitro models of thyroid cancer and determining whether growth on varying interfiber spacing changes the sensitivity of tumor cells to molecular inhibitors. Finally, although we did not identify transcriptional and metabolic changes that have been previously reported in regards to nuclear shape changes (76)(77)(78), we cannot exclude the possibility that chronic stresses and strain to nuclear shape associated with repeated cycles of attachment and recoil that were observed may have contributed to some of the transcriptional reprogramming and expression changes observed. We believe short-to long-term future studies using our platform provide novel quantifiable metrics to dissect whether acute nuclear shape changes vs. chronic stresses to nuclear shape associated with motility and recoil forces lead to distinct transcriptional responses.…”
Section: Discussionmentioning
confidence: 74%
“…Nuclear size and shape are important geometric parameters associated with cell integrity and functionality. 18,42 It is likely that changes in the size of the cell nucleus, as seen in this study, result from alterations in vesicular transport of proteins within the endoplasmic reticulum, and in nuclear envelope formation. 18,42,43 Changes in nuclear shape result from the reorganization of the nuclear lamina and are indicative of changes in nuclear stiffness and/or chromatin supraorganization and functionality.…”
Section: F I G U R E 5 Surface Plot Graphsmentioning
confidence: 75%
“…The median values of STT1 were 25.00 mm/min (range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] for the control group and 2.90 mm/min (range, 0-9) for the KCS group (P < .001). In relation to the TBUT, the median values were 10.00 seconds (range, 1-25) for the control group and 0.00 second (range, 0-8) for the KCS group (P < .001).…”
Section: Tear Productionmentioning
confidence: 99%
See 1 more Smart Citation